Pengaruh Kualitas Layanan terhadap Loyalitas Nasabah pada Jasa Travel - Didit Darmawan; Lailul Fuadah Firdaus (ProBisnis : Jurnal Manajemen, 2026)
Increasing competition in the travel service industry drives companies to continuously improve service quality in an effort to maintain customer loyalty. This research was conducted to examine the relationship between service quality and customer loyalty in the travel service sector. This study utilizes a literature review approach with a qualitative method that analyzes 10 national scientific articles from the 2020–2025 period, focusing on the link between service quality and customer loyalty through the roles of satisfaction and trust.The results of the analysis indicate that service quality plays a vital role in shaping customer loyalty, both directly and indirectly through customer satisfaction and trust. Satisfaction is formed when the service provided meets or exceeds customer expectations, while trust becomes a factor that strengthens the long-term relationship between customers and the company. Service quality dimensions such as reliability, responsiveness, assurance, empathy, and tangibles are the most influential aspects in shaping customer perceptions of travel services.Consequently, customer loyalty is influenced not only by the experience of using the service but also by how customers evaluate the overall service quality. This study confirms that consistently improving service quality is a key factor in maintaining customer loyalty in the travel service industry.